The Effect of Using Exoskeleton of Blue Crab (Callinectes sapidus) as a Dietary Calcium Source on the Egg Characteristics of Layer Hens (Gallus gallus domesticus) - Cueto, Kurt Nheil A. (Animo Repository, 2021)
The study focuses on the ability to use the exoskeleton of blue crab as alternative calcium and carotenoid supplement for layer hens and its effects on egg characteristics. Three groups of eighty layer hens each were fed a base feed formulation following the standards of the University of the Philippines Los Baños. The feeds were base feed as negative control (NG), a base feed with natural egg yolk colorants (capsorubin and lutein) as positive control (PG), and a base feed with 1% ground blue crab exoskeletons, as experimental (EG). The feeding lasted four weeks before egg collection. The eggs were weighed for their albumen, yolk, shell, and egg weight. The egg yolk color was determined using a DSM Fan and a digital Chroma meter, and the shell thickness using digital calipers. Statistical treatment was done through Kruskal Wallis test using SPSS software. Results showed that eggs of EG had significantly heavier shells with a mean of 5.93±0.11g, compared to 5.83±0.08g of the NG and 5.55±0.08g of the PG. Eggshell thickness was not significantly different among the three groups. Egg yolk color was significantly different in PG with a mean DSM gradient value of 11.96±0.11, compared to 5.92±0.14 of the NG and 6.48±0.20 of EG. Ground blue crab exoskeleton as a calcium supplement may increase the weight of the eggshells but may not intensify the egg yolk color.